Terahertz Optoelectronics: Design, Fabrication, and Modulation of THz Bandpass Metamaterials. Issue 11 (13th November 2019) - Wang, Qinghua; Gao, Bingtao; Raglione, Michaella; Wang, Huixin; Li, Baojia; Toor, Fatima; Arnold, Mark A.; Ding, Hongtao
Abstract : Interest in terahertz (THz) optoelectronics is driven by applications such as ultrawideband communication systems, atmospheric monitoring, airport security scanners, and biomedical imaging and sensing. In article number 1900071, Hongtao Ding and co‐workers give an overview of THz bandpass metamaterials, with a focus on the design strategies, fabrication techniques, modulation methods for transmission resonance, and applications.